A dynamic general equilibrium analysis of adaptation to climate change in Ethiopia - Sherman Robinson; Kenneth Strzepek; Dirk Willenbockel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This study links a multi-sectoral regionalized dynamic computable general equilibrium model of Ethiopia with a system of country-specific hydrology, crop, road and hydropower engineering models to simulate the economic impacts of climate change towards 2050. In the absence of externally funded policy-driven adaptation investments Ethiopia's GDP in the 2040s will be up to 10 percent below the counterfactual no-climate change baseline. Suitably scaled adaptation measures could restore aggregate welfare to baseline levels at a cost that is substantially lower than the welfare losses due to climate change.
Keywords: Q54; O55; D58; C68; 330; CGE analysis; global warming; growth; adaptation costs; development